Pengaruh Brand Image, Kualitas Produk, Lifestyle Dan Inovasi Produk Terhadap Keputusan Pembelian Smartphone Iphone - Azizah, Yasmin Nur; Rizal, Mohammad; Mahardani, Ahmad Subhan (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze the influence of Brand Image, Product Quality, Lifestyle, and Product Innovation on the Purchase Decision of iPhone smartphones. The research uses a quantitative approach, with a population of active students from the Faculty of Economics and Business at the Islamic University of Malang during the 2020-2023 period, with a sample of 110 respondents. Primary data was collected through a questionnaire method. The research results show that Brand Image, Product Quality, Lifestyle, and Product Innovation simultaneously have a significant effect on purchasing decisions. Partially, Brand Image, Product Quality, and Lifestyle have a significant effect, while Product Innovation has an insignificant effect on purchasing decisions. Keywords : Brand Image, Product Quality, Lifestyle, Product Innovation, and Purchase Decision.